Acknowledging mind power through NLP / Siti Nabilah Mohd Shaari - Mohd Shaari, Siti Nabilah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Faculty of Accountancy had organized a programme with aims to enhance students' confidence and self-esteem called Neuro-Linguistic Programme (NLP). This programme promoted students' confidence by acknowledging the role of the power of mind in achieving success by imagining the desired future. The future that is desired by a person will then be transferred into a picture that can be visualized by the person. This is a method called as "paint yourself". It is also the objective to improve students' confidence and to sow the percep-tion that dreams will come true if they are nurtured by high determination to achieve success.The programme was conducted by Ustaz Hamdi Rahman Mohd Yaacob, the Head of Unit Kepimpinan Pelajar, under Students' Affair Department, UiTM Perak Branch.The programme commenced at 8.30 a.m with the first session of introducing participant on the ob-jectives of the program, followed by team coaching slot that started at 11.00 a.m until 5.15 p.m. The programme concluded by naming three students to be awarded prizes for being able to visualize their future and turn it into a picture that can be visualized by that student.